2015
DOI: 10.1111/mec.13039
|View full text |Cite
|
Sign up to set email alerts
|

MHC variation reflects the bottleneck histories of New Zealand passerines

Abstract: Most empirical evidence suggests that balancing selection does not counter the effects of genetic drift in shaping postbottleneck major histocompatibility complex (MHC) genetic diversity when population declines are severe or prolonged. However, few studies have been able to include data from historical specimens, or to compare populations/species with different bottleneck histories. In this study, we examined MHC class II B and microsatellite diversity in four New Zealand passerine (songbird) species that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 67 publications
(180 reference statements)
3
44
1
Order By: Relevance
“…; Sutton et al . , ). This difference might be caused by the fact that GM represent different‐sized populations in a mutation–drift equilibrium (for neutral loci), rather than heavily bottlenecked populations where the loss of MHC allelic diversity might be reinforced by the interaction between drift and balancing selection (Ejsmond & Radwan ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Sutton et al . , ). This difference might be caused by the fact that GM represent different‐sized populations in a mutation–drift equilibrium (for neutral loci), rather than heavily bottlenecked populations where the loss of MHC allelic diversity might be reinforced by the interaction between drift and balancing selection (Ejsmond & Radwan ).…”
Section: Discussionmentioning
confidence: 99%
“…In populations with small effective population size (Ne), genetic drift has been shown to reduce MHC allelic diversity (Sutton et al . , ), thus counteracting the effect of PMBS (Robertson ; Kimura ; Miller & Lambert ). In several very small populations, MHC diversity was found to be even more reduced than neutral diversity (Sutton et al .…”
Section: Introductionmentioning
confidence: 99%
“…We amplified 18 microsatellite loci (see Table S1 in Supplementary Material) according to Sutton et al (2015). (Tallmon et al 2008).…”
Section: Microsatellite Genotypingmentioning
confidence: 99%
“…It has been shown that factors such as location of the population (insular or mainlandoriginating), bottleneck severity (duration and intensity) and prior history of bottlenecks, are all strong determinants of remaining genetic diversity in threatened species (e.g. Taylor & Jamieson 2008;Sutton et al 2015). However, it is currently unknown whether population bottleneck circumstance (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation